(untitled) (Experimental biology, 2019)
Composting WWS, manure and poultrymanureisone of the methods of bioconversion of organic waste, with which you can get environmentally friendly effective fertilizer. The most rational way to solve this problem is the composting of fermented sludge by solid-phase aerobic fermentation. The aim of the work is to screen actives trains for composting sewage sludge. Mesophilic and thermophilic bacteria were isolated from sludge and sewage from samples taken from sewage treatment plants in Astana and Karaganda for processing by composting sewage sludge to produce organic fertilizer. Screening of active strains of microorganisms by enzym aticactivity for composting sludge from sewage was carried out. The enzyme activity of the isolated strains was evaluated (lipase, amylolytic, proteolytic, cellulolytic, destructive with respect to oil and surfactant). Based on the results, 13 of the most active strains were selected. As a result of phenotypic and genetic identification, the isolated microorganisms were assigned to different physiological groups: Bacillusfusiformis, Pseudomonas lundensis, Bacillus amyloligiefaciens, Bacillus mojavensis, Enterobacter sp., Bacillus pumilus, Ochrobactrum sp., Bacillus coagulans, Enterobacter cloacae, Bacillus subtilis , Bacillus licheniformis, Bacillus clausii. Thus, as a result of the research, microorganisms were is olated and screening of active strainsof microorganisms wascarriedout for compostings ludgefrom wastewater. Keywords: microorganisms, sludgesediments, composting, wastewater.